Gaya Kepemimpinan Kepala Madrasah MI Ma’arif Bego dalam Meningkatkan Kemampuan Mengajar dan Motivasi Guru - Muhammad Majdi; Sartika Mei Mindasari; Jefri Faizal (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2020)
Education nowadays, to improve the performance of teachers continues to make various efforts to achieve goals and desires to achieve quality results. Therefore the leadership style implemented by the leadership of the organization is needed to discipline and control people in their work. Because basically the leadership style is important to do because of its function as an improvement tool for teachers. Teachers must show maximum performance in carrying out their duties and functions as educators, but still have the majority of teachers who have not shown good performance, and therefore the leadership style that will produce qualified educators to support supporting teaching and motivation of teachers. This type of research is a qualitative descriptive study that discusses events that occur in the field in the form of narration. To collect data in the field, researchers conducted interview observations, and documentation. The results of this study are the leadership styles that are applied by MI Ma'af idiot principals are the applied and transformational leadership styles. The leadership style can improve the performance of teachers in the school. And to complete this, researchers offered Ki Hajar Dewantara's leadership style to complete.,